The status of myopia refractive error from 2018 until 2021 among aged 30 to 35 years old in a private optometry practice, Dungun, Malaysia: retrospective data - Ithnin, Mohd. Hafidz; Othman, Shah Farez; Abd. Aziz, Nurul Ain; Mohd Adnan, Muhammad Ariff Haiqal (IIUM Press, 2023)
Introduction: Myopia or also known as near-sightedness is a common visual impairment. Myopia usually started in children and the changes does occur to individuals across age groups. It is tightly linked or commonly related among young individuals which are children and teenagers. Study or research regarding the refractive error changes among adults especially among pre-presbyopia age is under-explored as past research does not collect data for the changes among individuals aged more than 30 years. Aim: To evaluate the myopia refractive error changes among adults aged 30 to 35 years old at a private optometric practice, Dungun district, Terengganu state, Malaysia from 2018 until 2021. Methodology: This retrospective study was conducted at ArRayyan Optometry, Dungun, Terengganu. All patient record aged 30 to 35 years old from 2018 until at the practice were reviewed. Patients with record having history of ocular surgery as well as ocular and systemic diseases were excluded. The onset of myopia was stipulated at 14 years old. Demographic and mean spherical equivalent refractive error (SER) were collected and analysed. Results: Fifteen generally healthy myopic participants mean age of 33.07 ± 1.79 years were met the criteria stipulated. There was a statistically significant increment in myopia refractive error changes in adults aged 30 to 35 years old (p<0.001). Conclusion: Myopia refractive error changes could not only occur in children and teenagers but could also demonstrate in adults aged 30 to 35.